Evaluasi Tata Kelola Sistem Informasi Manajemen Sekolah dan Data Peserta Didik Berdasarkan Framework COBIT 2019 di SMAN 1 Medan - Oktaviana Bangun; Utari Adelia Citra; Chindy Olivia Melani; Putri Yolanda Purba; Ramadina Sofia Amadea (LOFIAN: Jurnal Teknologi Informasi dan Komunikasi, 2026)
The purpose of this study is to evaluate the School Management Information System and student data governance at Medan 1 Public High School (SMAN 1 Medan) using the COBIT 2019 framework. The evaluation was conducted across three key domains: grade and NISN (National Student Identity Number) data integrity (DSS06), e-learning availability (DSS05), and student data security. A quantitative approach was employed, with data collected through questionnaires, interviews, and direct observation of operational systems. The survey participants consisted of 45 individuals, including the principal, vice principal, teachers, IT staff, and system administrators. The analysis indicated that SMAN 1 Medan's IT governance maturity was at "Level 2 (Managed)" with an average score of 2.45 out of 5. The scores by domain were 2.38 for DSS06 (Business Process Control Management), 2.52 for DSS05 (Service Request and Incident Management), and 2.45 for the Data Security domain. Key findings from the study included the identification of several areas requiring improvement: (1) insufficient documentation for grade and NISN data management procedures, (2) e-learning infrastructure limitations that caused periodic downtime, and (3) suboptimal implementation of student data security policies. The study offers strategic recommendations for raising IT governance maturity to "Level 3 (Established)" through the implementation of standard operating procedures (SOPs), infrastructure improvements, and strengthening of information security policies.